COVID-19 Pneumonia in Children: From Etiology to Management - Parisi, Giuseppe Fabio; Indolfi, Cristiana; Decimo, Fabio; Leonardi, Salvatore; Miraglia del Giudice, Michele (Frontiers in Pediatrics, 2020)
COVID-19 is less serious in children than in adults. However, respiratory management dominates the clinical picture of hospitalized COVID-19 even in children. In some case series, deterioration of the clinical picture wherein dyspnea, cyanosis, and the onset of acute respiratory distress syndrome (ARDS) emerged ~8–10 days after the onset of SARS-CoV-2 infection, which could rapidly progress to multiple organ failure and death. This review aimed to evaluate the characteristics of COVID-19 pneumonia in pediatric populations, beginning from its etiology and pathological mechanisms and closing with its clinical management.